Method for controllably preparing nanoscale ultrathin graphdiyne and derivative thereof

Through the hard template method of controlling the expansion of copper substrate, the problem of preparing graphiteyne thin layer in the prior art is solved, and the preparation of high-quality, functional groups-free nano-sized ultra-thin graphiteyne and its derivatives is achieved, satisfying a variety of Application requirements.

CN119118109AActive Publication Date: 2024-12-13NANKAI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411289672.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-13
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

It is difficult to obtain high-quality small-layer or thin-layer graphite alkyne structures in batches, and alkyne bonds are prone to react under strong oxidation conditions, resulting in a decrease in the alkyne bond content in the structure and the difficult functional groups to remove affect subsequent applications.

Method used

The hard template method based on a controllable enlarged copper substrate is prepared by ball milling and sealed heating, and its intrinsic thin layer graphite acetic and its derivatives without functional groups, with a thickness of about 2 nanometers, which is suitable for a variety of graphite acetic derivatives. preparation.

Benefits of technology

It realizes the preparation of nano-level ultra-thin graphite acetic film with low cost, simple process and controllable quality, avoids the problems of alkyne bond reaction and the introduction of functional groups, and meets a variety of application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118109A_ABST
    Figure CN119118109A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano carbon material preparation, and discloses a method for controllably preparing nanoscale ultrathin graphdiyne and derivatives thereof. A substance A and a substance B are mixed and subjected to ball milling, mixed powder is obtained, the substance A is copper-containing salt, and the substance B is salt which is insoluble in acetone and pyridine, soluble in water or acid and not decomposed within 200 DEG C; putting the mixed powder into a closed heating environment, heating at 200-450 DEG C, cooling to room temperature, dropwise adding an acetone solution of graphdiyne or a derivative monomer thereof, maintaining the temperature for 1-2 days after dropwise adding, and cooling to room temperature; and soaking the powder with diluted hydrochloric acid for 1-3 days, carrying out suction filtration, and freeze-drying a filter cake to obtain the nanoscale ultrathin graphdiyne film. Compared with the prior art, the method has the advantages that the intrinsic thin-layer graphdiyne without other functional groups can be obtained, and the thickness is about 2 nanometers. Compared with an oxidation stripping method, the method has the advantages of low cost, simple process and controllable quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano carbon material preparation, in particular to a method for controllably preparing nano-scale ultra-thin graphyne and its derivatives. Background Art

[0002] Carbon materials have the advantages of being green, cheap, conductive, compatible, and easy to obtain. They are widely used in new energy fields such as electrocatalysis and energy storage. The carbon material family mainly includes graphite, graphene, fullerene, diamond, etc. Graphdiyne, independently developed by Chinese scientists in 2010, is different from the classical carbon material configuration. Alkyne bonds are uniformly introduced into the carbon skeleton. Under the premise of ensuring conductivity, the electron cloud density of the carbon skeleton is regulated. The uniform alkyne bonds bring rich physical and chemical properties to Graphdiyne, and there are novel discoveries in physical semiconductor sensing, new battery energy storage, electrocatalysis, and biological research. In addition, the bottom-up synthesis method can meet the preparation of a variety of derivatives. After continuous research by researchers around the world, the Graphdiyne family has gradually grown and has a wide variety of types. It can be designed according to needs to meet a variety of application research.

[0003] As a two-dimensional layered carbon material, obtaining thin or few-layer structures of graphyne has always been a difficult and important point in the preparation process. Conventional preparation methods can easily obtain micrometer-level or hundred-nanometer-level graphyne films, but it is difficult to obtain few-layer / thin-layer graphyne structures in batches. The currently reported preparation methods of few-layer graphyne are mainly based on the exfoliation method of graphene, and the intercalated oxygen functional groups are introduced through strong oxidation to help the stratification. However, acetylenic bonds are different from double bonds. Under strong oxidation conditions, acetylenic bonds are easy to react, which reduces the acetylenic bond content in the structure. At the same time, the strong oxidation process will also introduce a variety of oxygen-containing functional groups, which are difficult to remove, which will affect the subsequent further modification and application. Therefore, it is of great significance to develop an optimized preparation method to obtain intrinsic few-layer graphyne. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing nano-scale ultra-thin graphyne and its derivatives. Based on the strategy of controllable expansion of the copper substrate, intrinsic thin-layer graphyne films and thin-layer graphyne derivatives with uniform quality are prepared in batches from bottom to top by a hard template method, with a thickness of about 2 nanometers. Compared with the existing method of preparing thin-layer graphyne from top to bottom, the advantage of the present invention is that intrinsic thin-layer graphyne without other functional groups can be obtained, and the method is suitable for the thin-layer preparation of various graphyne derivatives. Compared with the oxidation exfoliation method, the present invention has the advantages of low cost, simple process and controllable quality.

[0005] The technical solution of the present invention to solve the technical problem is:

[0006] The present invention provides a method for preparing nanoscale ultra-thin graphyne and its derivatives, the method comprising the following steps:

[0007] (1) mixing substance A and substance B and ball-milling them to obtain a mixed powder of substance A and substance B, wherein substance A is uniformly dispersed on the surface of substance B, wherein substance A is a copper-containing salt, and substance B is a salt that is insoluble in acetone and pyridine, soluble in water or acid, and does not decompose within 200° C.;

[0008] (2) placing the mixed powder in a closed heating environment, heating it to 200-450° C. in an inert gas and hydrogen atmosphere, maintaining the hydrogen flow and the heating temperature for 2-4 hours, and then cooling it to room temperature;

[0009] (3) taking out the powder, adding it to a container, adding a solvent, and then dropping an acetone solution of graphyne or its derivative monomer, stirring at 50 to 180° C. until the addition is complete, maintaining the temperature for 1 to 2 days, and then cooling to room temperature;

[0010] (4) Pour out the liquid in the container after the reaction, rinse the powder, then soak the powder in dilute hydrochloric acid for 1 to 3 days, filter with deionized water, collect the filter cake, and obtain a nano-scale ultra-thin graphyne film by freeze drying.

[0011] Furthermore, in step (1), the mass ratio of substance A to substance B is 0.5 to 20:100 (preferably 5:100).

[0012] Furthermore, in step (1), substance A is one or more of copper nitrate, copper chloride, copper acetate, and copper sulfate, and may or may not contain water of crystallization;

[0013] Furthermore, in step (1), substance B is one or more of sodium chloride, sodium sulfate, sodium carbonate, potassium chloride, potassium sulfate, potassium carbonate, calcium chloride, calcium sulfate, calcium carbonate, magnesium chloride, magnesium sulfate, magnesium carbonate, barium carbonate, barium sulfate, and silicon dioxide. Sodium chloride is preferred.

[0014] Preferably, in step (1), when substance A and substance B are mixed and ball-milled, the total ball-milling time is not less than 3 hours, and the obtained mixed powder needs to be sieved to ensure uniform particles, which can meet the 200 mesh sieve.

[0015] Preferably, in step (1), the obtained solid powder is stored in a dry environment to prevent the copper from being oxidized again and to avoid agglomeration.

[0016] Furthermore, in step (2), the closed heating environment is a tubular furnace, and the inert gas is nitrogen or argon, preferably argon.

[0017] Furthermore, in step (2), the heating rate from room temperature to 200-450°C is 3-10°C / min, preferably 5°C / min. The temperature should be selected to ensure that substance B does not decompose, and copper reduction can be achieved at temperatures above 200°C.

[0018] Furthermore, in step (2), the gas flow ratio of hydrogen to inert gas is 1:3 to 1:1. Preferably, 40 to 100 sccm hydrogen is mixed with 120 to 300 sccm argon. More preferably, 50 sccm hydrogen is mixed with 150 sccm argon.

[0019] Furthermore, in step (2), the mixed powder is reduced for 2 to 4 hours, which can be adjusted according to the amount of the mixed powder added. After the mixed powder is reduced, it is pink and should be used immediately or stored in a dryer / glove box. Avoid prolonged exposure to humid air to prevent re-oxidation.

[0020] Furthermore, in step (3), the mass ratio of the powder to the graphyne or its derivative monomer is 100:0.5 to 100:3.

[0021] Furthermore, in step (3), the solvent is a mixed solvent of acetone, pyridine and tetramethylethylenediamine prepared in a volume ratio of 100:5:1. Preferably, in step (3), the amount of acetone added in advance and the amount of acetone used to dissolve hexaphenylbenzene are calculated together to a ratio of 100:5:1. For example, preferably, 50 ml of acetone, 5 ml of pyridine and 1 ml of tetramethylethylenediamine are added to a three-necked flask in advance, and 50 ml of acetone is used to dissolve hexaphenylbenzene and is added dropwise to the system.

[0022] Furthermore, in step (3), 1,3,5-triynylbenzene, 1,3,5-triethynyl-2,4,6-trifluorobenzene or other graphyne derivative monomers can replace hexaynylbenzene to polymerize to obtain ultrathin nanoscale graphyne derivatives with different structures.

[0023] Furthermore, in step (3), the monomer solution is added dropwise within 2 hours. After the addition is completed, stirring can be stopped.

[0024] Furthermore, in step (4), the powder is rinsed with N,N-dimethylformamide and acetone for 2 to 3 times respectively, and the last time is rinsed with acetone, and then dried at room temperature.

[0025] Furthermore, in step (4), the concentration of the dilute hydrochloric acid selected is 0.5 to 1 M, and the soaking time is not less than two days. The mixture can be left exposed to facilitate the oxidation of copper.

[0026] Furthermore, in step (4), the mixture is washed with deionized water until the pH value of the system is 7, the filter cake is collected, and the remaining water is removed by freeze drying at -20 to -60°C. High-temperature drying can easily cause the material to agglomerate and destroy the microscopic morphology, so high-temperature drying should be avoided.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) Based on the strategy of controllable expansion of the copper substrate, the present invention combines the regulation of the monomer input ratio to innovatively prepare an intrinsic few-layer nanoscale graphyne structure, and changes the polymerized monomer to achieve the preparation of a variety of graphyne derivative few-layer structures.

[0029] (2) The present invention is based on a hard template growth strategy and selects soluble, cheap and stable salt crystals as templates, which effectively realizes the controllable expansion of the growth substrate and its easy removal.

[0030] (3) The present invention achieves controllable preparation of nanostructures with different growth thicknesses, which can be as low as 1 nanometer, by adjusting the copper loading ratio and the amount of mixed powder and monomer input. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the XRD pattern of the nano-scale ultra-thin graphyne prepared in Example 1 of the present invention;

[0032] Figure 2 The Raman result of the nano-scale ultra-thin graphyne prepared in Example 1 of the present invention;

[0033] Figure 3 This is a SEM image of the nanoscale ultra-thin graphyne prepared in Example 1 of the present invention;

[0034] Figure 4 TEM image of nano-scale ultra-thin graphyne prepared in Example 1 of the present invention;

[0035] Figure 5 This is a high-magnification TEM image of the nanoscale ultra-thin graphyne prepared in Example 1 of the present invention;

[0036] Figure 6 This is an AFM image of the nanoscale ultra-thin graphyne prepared in Example 1 of the present invention;

[0037] Figure 7 This is the XRD pattern of the nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 2 of the present invention;

[0038] Figure 8 This is a SEM image of the nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 2 of the present invention;

[0039] Fig. 9 TEM image of nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 2 of the present invention;

[0040] Fig.10 This is an AFM image of the nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 2 of the present invention;

[0041] Fig.11 This is a SEM image of the nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 3 of the present invention;

[0042] Fig.12 TEM image of nanoscale ultra-thin hydrogen-substituted graphyne prepared in Example 3 of the present invention;

[0043] Fig.13 This is an AFM image of the nanoscale ultra-thin graphyne prepared in Example 4;

[0044] Fig.14 This is the AFM image of the nanoscale ultrathin graphyne prepared in Example 5. DETAILED DESCRIPTION

[0045] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of the present invention.

[0046] Example 1

[0047] A method for preparing nanoscale ultra-thin graphyne and its derivatives comprises the following steps:

[0048] (1) 50 g of sodium chloride and 2.5 g of copper acetate were mixed and ball-milled for 5 hours, and then the mixed powder after ball milling was sieved through 200 mesh. The powder after ball milling was light blue.

[0049] (2) 6 g of the mixed powder was placed in two quartz boats and placed in a closed heating tube furnace; in a hydrogen and argon mixed atmosphere, the temperature was raised to 300°C at a rate of 5°C / min, with a hydrogen gas flow rate of 50 sccm and a mixed argon gas flow rate of 150 sccm; after maintaining the temperature at 300°C for two hours, the hydrogen was turned off and the argon gas was kept flowing, and the system was naturally cooled to room temperature. The powder was taken out and was pink in color.

[0050] (3) Take 2 g of the pink powder obtained in step (2) and place it in a 250 ml three-necked flask, replace the air in the flask with an inert gas atmosphere, and add a magnet. Then inject 50 ml of acetone, 5 ml of pyridine, and 1 ml of tetramethylethylenediamine into the system and stir. Add 50 ml of acetone solution containing 30 mg of hexaynylbenzene into the system through a constant pressure dropping funnel, and add the solution within two hours. After the addition is complete, turn off the stirring, heat the system to 60°C and maintain it for 24 hours. Then stop heating and cool naturally to room temperature.

[0051] (4) Filter the powder obtained in step (3), and rinse the powder alternately with N,N-dimethylformamide and acetone, and rinse with acetone for the last time, and then dry the powder naturally. Soak the powder in dilute hydrochloric acid for 2 days to dissolve the copper species in the powder. Wash the powder with ultrapure water until the pH value of the system is 7, disperse the powder in a small amount of deionized water, freeze it with liquid nitrogen, and place it in a vacuum freeze dryer at -55°C to obtain the final nano-scale ultra-thin graphyne powder.

[0052] Depend on Figure 1 It can be seen that the main diffraction peaks of the obtained nanoscale ultrathin graphyne powder XRD are carbon (002) and (101) crystal planes, and the interlayer spacing is 0.353 nm.

[0053] Depend on Figure 2 It can be seen that the Raman spectrum of the obtained nano-scale ultra-thin graphyne powder is at 2220 cm – 1 There are obvious alkyne bond signals.

[0054] Depend on Figure 3 It can be seen that the obtained nano-scale graphyne powder is an independent nanosheet with a thickness of nanometer scale.

[0055] Depend on Figure 4 It can be seen that the obtained nano-scale graphyne powder is a uniform thin layer peeled off from the sodium chloride particles.

[0056] Depend on Figure 5 It can be seen that the obtained nanoscale graphyne powder is a nano-flake with uniform thickness at the microscopic level.

[0057] Depend on Figure 6 It can be seen that the obtained nano-scale graphyne powder has an average thickness of 1 to 2 nm.

[0058] Example 2

[0059] The difference between Example 2 and Example 1 is that the hexaynylbenzene in step (3) is changed to 1,3,5-triynylbenzene. The rest is the same as Example 1.

[0060] Depend on Figure 7 It can be seen that the XRD of the nanoscale hydrogen-substituted graphyne powder obtained in Example 2 is still (002) crystal plane and (101) crystal plane, and the interlayer spacing is 0.356 nanometers.

[0061] Depend on Figure 8 It can be seen that when the added polymerization monomer is 1,3,5-triynylbenzene, ultrathin nanosheets formed by interweaving nanofibers can be grown.

[0062] Depend on Fig. 9 It can be seen that the nanoscale hydrogen-substituted graphyne powder obtained in Example 2 is composed of interwoven thin layer fibers.

[0063] Depend on Fig.10 It can be seen that the nanoscale hydrogen-substituted graphyne powder obtained in Example 2 is composed of nanofibers with a thickness of about 2.3 nm.

[0064] Example 3

[0065] The difference between Example 3 and Example 2 is that the sodium chloride in step (1) is changed to sodium sulfate. The rest is the same as Example 2.

[0066] Depend on Fig.11 and Fig.12 It can be seen that when the template is changed to sodium sulfate, a fiber-interwoven thin layer of hydrogen-substituted graphyne film can still be obtained.

[0067] Example 4

[0068] The difference between Example 4 and Example 1 is that the mass of hexaynylbenzene in step (3) is changed to 40 mg. The other parts are the same as Example 1.

[0069] Depend on Fig.13 It can be seen that the thickness of the nano-scale graphyne powder obtained in Example 4 is about 5.4 nm.

[0070] Example 5

[0071] The difference between Example 5 and Example 1 is that the mass of hexylbenzene in step (3) is changed to 60 mg, and the mass of the powder sample in step (2) is changed to 2.5 g. The rest is the same as Example 1.

[0072] Depend on Fig.14 It can be seen that the thickness of the nano-scale graphyne powder obtained in Example 5 is about 10.52 nm.

[0073] Any matters not described in the present invention are applicable to the prior art.

[0074] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for controllably preparing nano-scale ultra-thin graphyne and its derivatives, It is characterized in that The following steps are involved: (1) mixing substance A and substance B and ball-milling them to obtain a mixed powder of substance A and substance B, wherein substance A is uniformly dispersed on the surface of substance B, wherein substance A is a copper-containing salt, and substance B is a salt that is insoluble in acetone and pyridine, soluble in water or acid, and does not decompose within 200° C.; (2) placing the mixed powder in a closed heating environment, heating it to 200-450° C. in an inert gas and hydrogen atmosphere, maintaining the hydrogen flow and the heating temperature for 2-4 hours, and then cooling it to room temperature; (3) taking out the powder, adding it to a container, adding a solvent, and then dropping an acetone solution of graphyne or its derivative monomer, stirring at 50 to 180° C., stopping stirring after the dropwise addition is completed, maintaining the temperature for 1 to 2 days, and then cooling to room temperature; (4) Pour out the liquid in the container after the reaction, rinse the powder, then soak the powder in dilute hydrochloric acid for 1 to 3 days, filter with deionized water, collect the filter cake, and obtain a nano-scale ultra-thin graphyne film by freeze drying.

2. The method for controllably preparing nanoscale ultrathin graphyne and its derivatives according to claim 1, It is characterized in that In step (1), the mass ratio of substance A to substance B is 0.5 to 20:

100.

3. The method for controllably preparing nanoscale ultra-thin graphyne and its derivatives according to claim 1, It is characterized in that In step (1), the substance A is one or more of copper nitrate, copper chloride, copper acetate, and copper sulfate, and may or may not contain water of crystallization.

4. The method for controllably preparing nanoscale ultrathin graphyne and its derivatives according to claim 1, It is characterized in that In step (1), the substance B is one or more of sodium chloride, sodium sulfate, sodium carbonate, potassium chloride, potassium sulfate, potassium carbonate, calcium chloride, calcium sulfate, calcium carbonate, magnesium chloride, magnesium sulfate, magnesium carbonate, barium carbonate, barium sulfate, and silicon dioxide.

5. The method for controllably preparing nanoscale ultra-thin graphyne and its derivatives according to claim 1, It is characterized in that In step (2), the gas flow ratio of hydrogen to inert gas is 1:3 to 1:

1.

6. The method for controllably preparing nanoscale ultra-thin graphyne and its derivatives according to claim 1, It is characterized in that In step (3), the mass ratio of the powder to the graphyne or its derivative monomer is 100:0.5 to 100:

3.

7. The method for controllably preparing nanoscale ultra-thin graphyne and its derivatives according to claim 1, It is characterized in that In step (3), the graphyne monomer and its derivatives are one or more of hexaynylbenzene, 1,3,5-triynylbenzene, and 1,3,5-triethynyl-2,4,6-trifluorobenzene.

8. The method for controllably preparing nanoscale ultra-thin graphyne and its derivatives according to claim 1, It is characterized in that In step (3), the solvent is a mixed solvent of acetone, pyridine and tetramethylethylenediamine prepared in a volume ratio of 100:5:1.

Citation Information

Patent Citations

  • Graphite alkene nanotube and preparation method thereof

    CN102205959A

  • A carbon nanomaterial and its application in sodium ion battery

    CN108987750A

  • Preparation method for in-situ synthesis three-dimensional graphene / one-dimensional carbon nanotube-supported copper nanoparticle material

    CN110576187A

  • Preparation method of ultrathin nanoscale graphdiyne film

    CN110668436A

  • Graphdiyne nanotube and preparation method thereof

    CN113912041A